The causal association between circulating cytokines with the risk of frailty and sarcopenia under the perspective of geroscience - Wang, Congzhi; Wang, Jiazhi; Wan, Rui; Kurihara, Hiroshi; Wang, Min (Frontiers in Endocrinology, 2024)
Introduction: Circulating cytokines were considered to play a critical role in the initiation and propagation of sarcopenia and frailty from observational studies, this study aimed to find the casual association between circulating cytokines and sarcopenia and frailty from a genetic perspective by twosample Mendelian randomization analysis.Methods: Data for 41 circulating cytokines were extracted from the genome-wide association study (GWAS) dataset of 8293 European participants. Inverse-variance weighted (IVW) method, Mendelian randomization (MR) Egger, and weighted median method were applied to assess the relationship of circulating cytokines with the risk of aging-related syndromes and frailty. Furthermore, MR-Egger regression was used to indicate the directional pleiotropy, and Cochran's Q test was used to verify the potential heterogeneity. The "leave-one-out" method was applied to visualize whether there was a causal relationship affected by only one anomalous single nucleotide variations (SNPs).Results: Genetic predisposition to increasing levels of interleukin-10 (IL-10), interleukin-12 (IL-12), and vascular endothelial growth factor (VEGF) was associated with the higher risk of low hand grip strength according to the inverse-variance weighted method (R=1.05, 95% CI=1.01-1.10, P=0.028, FDR-adjusted P=1.000; OR=1.03, 95% CI=1.00-1.07, P=0.042, FDR-adjusted P=0.784; OR=1.02, 95% CI=1.00-1.05, P=0.038, FDR-adjusted P=0.567). Furthermore, genetically determined higher macrophage colonystimulating factor (M-CSF) were associated with a lower presence of appendicular lean mass (OR=1.01, 95% CI=1.00-1.02, P=0.003, FDR-adjusted P=0.103). Monokine induced by interferon-gamma (MIG) and tumor necrosis factor-beta (TNF-β) were associated with a higher risk of frailty (OR=1.03, 95% CI=1.01-1.05, P<0.0001, FDR-adjusted P=0.012) (OR=1.01, 95% CI=1.00-1.03, P=0.013, FDR-adjusted P=0.259). Regarding the heterogeneity and horizontal pleiotropy of this study, we didn't find between the circulating cytokines and the risk of frailty and sarcopenia.Genetic predisposition to assess IL-10, IL-12, and VEGF levels associated with a higher risk of low hand grip strength, Macrophage colony-stimulating factor M-CSF with the presence of appendicular lean mass. the high levels of TNF-β and MIG were associated with a higher risk of frailty. More studies will be required to explore the molecular biological mechanisms underlying the action of inflammatory factors.